Spray-dried powders enhance vaginal siRNA delivery by potentially modulating the mucus molecular sieve structure - Wu N (Dove Medical Press, 2015)
Na Wu,1,2,* Xinxin Zhang,2,* Feifei Li,2 Tao Zhang,2 Yong Gan,2 Juan Li1 1School of Pharmacy, China Pharmaceutical University, Nanjing, People’s Republic of China; 2Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Vaginal small interfering RNA (siRNA) delivery provides a promising strategy for the prevention and treatment of vaginal diseases. However, the densely cross-linked mucus layer on the vaginal wall severely restricts nanoparticle-mediated siRNA delivery to the vaginal epithelium. In order to overcome this barrier and enhance vaginal mucus penetration, we prepared spray-dried powders containing siRNA-loaded nanoparticles. Powders with Pluronic F127 (F127), hydroxypropyl methyl cellulose (HPMC), and mannitol as carriers were obtained using an ultrasound-assisted spray-drying technique. Highly dispersed dry powders with diameters of 5–15 µm were produced. These powders showed effective siRNA protection and sustained release. The mucus-penetrating properties of the powders differed depending on their compositions. They exhibited different potential of opening mesh size of molecular sieve in simulated vaginal mucus system. A powder formulation with 0.6% F127 and 0.1% HPMC produced the maximum increase in the pore size of the model gel used to simulate vaginal mucus by rapidly extracting water from the gel and interacting with the gel; the resulting modulation of the molecular sieve effect achieved a 17.8-fold improvement of siRNA delivery in vaginal tract and effective siRNA delivery to the epithelium. This study suggests that powder formulations with optimized compositions have the potential to alter the steric barrier posed by mucus and hold promise for effective vaginal siRNA delivery. Keywords: siRNA delivery, vaginal administration, spray-dried powders, mucus penetration, molecular sieve effect